Stone-like material as well as preparation method and application thereof
By using raw materials such as vanadium-titanium metallurgy slag, copper metallurgy slag, waste ceramics and waste microcrystalline glass, and through sintering, cooling and grinding processes, the problem of insufficient wear resistance of existing imitation stone materials has been solved, and the mechanical properties and wear resistance have been improved, and the resource utilization of waste is achieved.
Patent Information
- Application Number
- CN202411788027.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-06
AI Technical Summary
While improving mechanical properties, existing imitation stone materials have limited wear resistance and complex processes and are difficult to practice.
Vanadium-titanium metallurgy slag, copper metallurgy slag, waste ceramics and waste microcrystalline glass are used as raw materials, recrystallization and structural reconstruction are carried out through sintering and cooling processes, and the particle size of copper metallurgy slag and the ratio of nucleating agent is optimized to form a high density and high wear resistance imitation stone material.
It has achieved improvements in the mechanical properties of imitation stone materials (such as flexural strength) and wear resistance, and at the same time, it has effectively utilized metallurgical solid waste, which has high environmental value and economic benefits.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stone imitation materials, and in particular to a stone imitation material and a preparation method and application thereof. Background Art
[0002] China is a big consumer of stone. With the rampant development of natural stone and the increasing scarcity of natural resources, it is an inevitable trend for artificial stone to gradually replace natural stone. Stone-like materials are mainly divided into organic-inorganic composite and pure inorganic materials. Sintered stone-like materials are praised and paid attention to by more and more consumers because of their natural texture and color and excellent stone-like properties. In recent years, the preparation of different types of solid waste as raw materials has attracted more and more attention from researchers. At present, the most commonly used solid waste raw materials are metallurgical slag, fly ash, red mud, tailings, ceramic waste, etc.
[0003] At present, scholars seek to improve the mechanical properties of materials through various technical means, such as introducing mullite, cordierite, quartz and aluminum-rich crystal phases from the raw material end to control the physical components of the stone-like materials to achieve the purpose of improving mechanical strength (such as flexural strength). However, with the deepening of research and the expansion of the application of stone-like materials, while meeting the improvement of mechanical properties, there is little discussion on the wear resistance of stone-like materials. Although there are process means to control the crystal size and structure, these process means are complex and have limited effect on improving wear resistance, and are not easy to implement in practice. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the prior art to at least a certain extent. To this end, one purpose of the present invention is to propose a method for preparing a stone-like material, wherein the raw materials include 20-40 parts of vanadium-titanium metallurgical slag, 20-40 parts of copper metallurgical slag, and 30-60 parts of nucleating agent by weight; the nucleating agent includes waste microcrystalline glass and waste ceramics in a mass ratio of 1: (0.5-3). Vanadium-titanium metallurgical slag and copper metallurgical slag are introduced from the raw material end, which contain a large amount of amorphous substances such as glass phase, and can be recrystallized and restructured through heat treatment processes such as sintering process and cooling process control, thereby improving the mechanical properties (such as flexural strength) and wear resistance of the stone-like material; at the same time, these raw materials are produced in large quantities and are difficult to use on a large scale. The preparation method of the stone-like material provided by the present invention can effectively utilize these waste materials, realize waste resource utilization, and have high environmental value.
[0005] Waste ceramics and waste glass-ceramics also have rich glass-like amorphous substances. As nucleating agents, on the one hand, they can realize the resource utilization of waste materials and achieve environmental protection value. On the other hand, during the sintering and cooling process, waste glass-ceramics and waste ceramics are conducive to the formation of crystal nuclei and the preparation of stone-like materials with high wear resistance, especially when the mass ratio of waste glass-ceramics to waste ceramics is 1: (0.5-3), waste glass-ceramics and waste ceramics can work synergistically to make the wear resistance and mechanical properties (such as flexural strength) of the obtained stone-like materials more significantly improved.
[0006] In some embodiments, the preparation method includes: powdering, molding, sintering and cooling the raw materials; wherein the sintering process is: heating from room temperature to a softening nucleation temperature of 850-1000°C at a heating rate of 5-10°C / min, and keeping the temperature for at least 0.5 hours; then heating to a firing temperature of 1120-1200°C at a rate of 3-8°C / min, and keeping the temperature for 2-5 hours. The above sintering process is conducive to the rapid formation of crystal nuclei and the formation of a crystal structure of suitable size, completeness and uniformity, thereby improving the mechanical properties and wear resistance of the imitation stone material.
[0007] In some embodiments, the cooling process is: first cooling from the sintering temperature to the crystallization temperature at a rate of 3-5°C / min, and keeping at the crystallization temperature for 1-6 hours; then cooling from the crystallization temperature to room temperature at a rate of 4-6°C / min. Preferably, the crystallization temperature is 950-980°C; preferably, keeping at the crystallization temperature for 3-4 hours.
[0008] The above cooling process is conducive to forming a complete and uniform crystal structure with a suitable grain size, while improving the purity of the crystallized product, thereby further improving the mechanical properties and wear resistance of the stone-like material.
[0009] In some embodiments, the powder making process is: the raw material and the dispersant are wet-ground, mixed evenly to obtain a slurry, dried, granulated and aged; wherein after granulation, the grinding particle size of the raw material is 325 mesh-400 mesh. The internal structure of copper metallurgical slag is hard and brittle, easy to break and difficult to grind. The use of a grinding process to introduce copper metallurgical slag and combined with raw material particle size control can effectively improve the wear resistance and density of the imitation stone material.
[0010] In some embodiments, the slurry is dried at a temperature of 100-120°C.
[0011] In some embodiments, the moisture content of the dried powder is 5-7%.
[0012] In some embodiments, the aging time is 24-48 hours.
[0013] In some embodiments, the molding pressure is 30-40 MPa, and the pressure is maintained for 5-10 seconds. Molding under such conditions can effectively remove internal gas, which is conducive to forming a dense structure during the sintering process.
[0014] In some embodiments, the dispersant is selected from at least one of sodium silicate aqueous solution, sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate. The dispersant can achieve uniform inclusion of the slurry solid phase and liquid phase, good slurry fluidity and compatibility.
[0015] The second aspect of the present invention provides a stone-like material, which is prepared by the above-mentioned preparation method. Compared with traditional stone-like materials, the stone-like material provided by the present invention has excellent properties such as high flexural strength and high wear resistance; the use of metallurgical solid waste to prepare wear-resistant stone-like materials can greatly reduce material costs and achieve the purpose of resource utilization.
[0016] The third aspect of the present invention provides the use of the stone-like material in at least one of architecture, interior decoration, garden landscape, and artwork.
[0017] Preferably, the application in the building includes at least one of exterior wall facades, interior wall decorative tiles and antique floor tiles.
[0018] Preferably, the application in the interior decoration includes using the imitation stone material as at least one of door sills, window sills, and cabinet countertops. Preferably, the application in the garden landscape includes at least one of walkways, rockery, and corridor decoration.
[0019] Preferably, the application in the artwork includes at least one of a vase, a sculpture, and an artifact component.
[0020] The use of the imitation stone material to replace natural stone can avoid the possible radioactive contamination of natural stone, and the imitation stone material can use metallurgical waste slag as raw material, and can achieve quantitative production to achieve the purpose of reducing costs; more personalized products can also be produced and manufactured according to market demand to meet the personalized needs of the market, such as color, pattern, size, etc.
[0021] The present invention has at least the following technical effects: (1) Mainly introduce vanadium-titanium metallurgical slag, copper metallurgical slag, waste ceramics, waste microcrystalline glass, etc. from the raw material end, which contains a large amount of amorphous substances such as glass phase, and recrystallize and reconstruct the structure through heat treatment processes such as sintering process and cooling process control; thereby achieving the improvement of mechanical properties and wear resistance of imitation stone materials; (2) Copper metallurgical slag is mainly composed of iron, silicon and oxygen, and these three elements account for more than 80% of the total mass. From the perspective of mineral composition, the main mineral components of copper slag are amorphous glass composed of fayalite (Fe2SiO4), magnetite (Fe3O4) and some gangue. The internal structure is hard and brittle, easy to break and difficult to grind. When added to the formula system through the grinding process, the iron-containing component can be used as a sintering aid for stone-like materials on the one hand, and on the other hand, it forms new crystal phases such as olivine and spinel. (3) Since the raw materials are mostly made of materials that have undergone heat treatment such as metallurgy, the sintering performance of the raw materials is relatively stable, which reduces product defects. Through customized selection of raw materials and process control, stone-like materials with both structure and function are prepared, which realizes the resource utilization of solid waste and has good economic, social and ecological benefits.
[0022] Specific implementation method.
[0023] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0024] In the prior art, when solid waste is used as raw material to prepare stone-like materials, the resulting stone-like materials often have poor wear resistance, or the problem of not being able to achieve both wear resistance and flexural strength. In order to improve wear resistance, attempts have been made to regulate the crystal structure and size, generally by adjusting the sintering and cooling processes, such as temperature, temperature change rate, etc. However, the process is complicated and has limited effect on improving wear resistance, and is not easy to implement in practice.
[0025] Based on this, the present invention provides a highly wear-resistant stone-like material and a preparation method and application thereof from the perspective of compatibility of wear resistance and strength (such as flexural strength) in stone-like materials. The selection and optimization are carried out in terms of raw material selection and firing and cooling process regulation to solve the problems of wear resistance and flexural strength in the prior art and achieve the purpose of preparing highly wear-resistant stone-like materials. At the same time, the preparation method provided by the present invention has a relatively high firing temperature and a short firing cycle.
[0026] In one aspect of the present invention, a method for preparing a stone-like material is proposed. The raw materials include 20-40 parts of vanadium-titanium metallurgical slag, 20-40 parts of copper metallurgical slag, and 30-60 parts of a nucleating agent, and the nucleating agent is selected from waste ceramics and waste microcrystalline glass, and the amount of waste ceramics is 20-30 parts, and the amount of waste microcrystalline glass is 10-30 parts; preferably, the total weight is 100 parts, wherein, in the following embodiments, 1 part = 1 kg.
[0027] The vanadium-titanium metallurgical slag can be 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or other parts by weight, or a range of these parts, such as 20-35 parts, 20-30 parts, 20-25 parts, 25-40 parts, 30-40 parts, 25-35 parts, etc.; the copper metallurgical slag can be 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or other parts by weight, or a range of these parts, such as 20-35 parts, 20-30 parts, 20-25 parts, 25-40 parts, 30-40 parts, 25-35 parts, etc. 5 parts, etc.; the amount of nucleating agent is 30 parts, 40 parts, 50 parts, 60 parts or other parts by weight, or it can be a range of these parts, among which the amount of waste ceramics is 20 parts, 25 parts, 30 parts or other parts by weight, or it can be a range of these parts, such as 20-25 parts, 25-30 parts, etc., the amount of waste microcrystalline glass is 10 parts, 15 parts, 20 parts, 25 parts, 30 parts or other parts by weight, or it can be a range of these parts, such as 10-25 parts, 20-30 parts, 15-25 parts, etc.
[0028] The method for preparing the stone-like material provided by the embodiment of the present invention comprises the following steps.
[0029] (1) Raw material grinding: Wet grind the raw materials and additives in the formula amount.
[0030] (2) Drying: After fully mixing the ground raw materials and additives, a formula slurry is obtained, and the slurry is placed in an oven and the oven temperature is adjusted to 100-120°C for drying; the drying temperature can be 100°C, 105°C, 110°C, 115°C, 120°C or other temperatures, and can also be a range of these temperatures.
[0031] (3) Granulation: After drying, the powder is sieved through a 40-mesh sieve according to a moisture content of 5-7%, and then aged for 24-48 hours. The moisture content of the powder after drying can be 5%, 6%, 7%, or a range of these moisture contents. After granulation, the aging time can be 24h, 36h, 48h, or other time or a range of these time.
[0032] (4) Molding: Molding pressure is 20-40MPa, and demolding is performed after holding the pressure for 5-10 seconds. During the molding process, the pressure can be 20MPa, 30MPa and 40MPa or other pressures or a pressure range composed of these pressures, and the holding time can be 5s, 7s, 8s and 10s or other time or a time range composed of these time.
[0033] (5) Sintering: Raise the temperature from room temperature to the softening nucleation temperature of 850-1000°C at a heating rate of 5-10°C / min, and keep it at that temperature for at least 0.5 hour; then raise the temperature to the sintering temperature of 1120-1200°C at a rate of 3-8°C / min, and keep it at that temperature for 2-5 hours; during the sintering process, the heating rate from room temperature to the softening nucleation temperature can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min and 10°C / min or other rates or a range of these rates; the softening nucleation temperature can be 850°C, 900°C, 950°C, 1000°C or other temperatures, also It can be a range of these temperatures; the holding time at the softening nucleation temperature can be 0.5h, 1h, 1.5h, 2h or other times, or a time range composed of these times; the rate of heating to the sintering temperature can be 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min or other rates or a range composed of these rates; the sintering temperature can be 1120℃, 1150℃ and 1200℃ or other temperatures or a temperature range composed of these temperatures, and the holding time can be 2h, 3h, 4h and 5h or other times or a time range composed of these times.
[0034] (6) Cooling: First cool from the sintering temperature to the crystallization temperature at a rate of 3-5°C / min, and keep it at the crystallization temperature for 1-6 hours; then cool from the crystallization temperature to room temperature at a rate of 4-6°C / min. The cooling rate from the sintering temperature to the crystallization temperature can be 3°C / min, 4°C / min, 5°C / min or other rates or a range of these rates; the keeping time at the crystallization temperature can be 1h, 2h, 3h, 4h, 5h, 6h or other time or a range of these times; the cooling rate from the crystallization temperature to room temperature can be 4°C / min, 5°C / min, 6°C / min or other rates or a range of these rates.
[0035] Among them, the additive is a dispersant selected from sodium silicate aqueous solution (commonly known as water glass), sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate.
[0036] During the cooling process, the crystallization temperature is 950°C-980°C, such as 950°C, 960°C, 970°C, 980°C or other temperatures or temperature ranges composed of these temperatures, and the holding time at the crystallization temperature is preferably 3-4h, such as 3h, 4h, 3.5h or other times or time ranges composed of these times.
[0037] The above parameters are only examples and are not intended to be limiting. Those skilled in the art may make selections based on actual conditions.
[0038] Copper metallurgical slag (also called copper slag) is black or brown, with a metallic luster on the surface and a true density of 3.5 to 4.5 t / m 3 The internal structure of copper slag is hard and brittle, easy to break and difficult to grind. It is generally used as a raw material in cement, sandstone aggregate, cast stone, roadbed material, etc., but generally, millimeter-level copper slag is directly added to cement-based materials as aggregate and support material. It has been verified that when added to the formula of imitation stone materials in this way and sintered and cooled, there will be problems such as high sintering temperature, low material densification, poor wear resistance (generally need to reach 1250°C), and long sintering cycle (generally 5-8 hours); in the present invention, the copper metallurgical slag is added to the formula system through a grinding process to control the particle size of the copper metallurgical slag to 325-400 meshes. On the one hand, the iron-containing component can be used as a sintering aid for the imitation stone material, and on the other hand, new crystalline phases such as olivine and spinel are formed. At the same time, the problems of high sintering temperature and long sintering cycle of copper slag in the prior art are overcome. Copper slag and vanadium-titanium metallurgical slag are combined, and under the action of a nucleating agent, the crystal structure can be reshaped through sintering and cooling processes, thereby improving the wear resistance and flexural strength of the imitation stone material.
[0039] The preparation method provided in the embodiment of the present invention utilizes metallurgical slag (vanadium-titanium metallurgical slag and copper metallurgical slag) that has undergone thermal treatment, waste ceramics, waste microcrystalline glass, etc., which contain a large amount of amorphous glass phase characteristics and the stability of clinker, realizes secondary reconstruction of crystals through firing, and optimizes the process to prepare high-density stone-like materials, and greatly enhances the mechanical strength of the stone-like materials, especially the flexural strength and wear resistance; at the same time, it realizes the resource utilization of waste materials and achieves economic, social and ecological benefits.
[0040] In a second aspect, a stone-like material is provided, which is prepared by the preparation method. The water absorption rate of the stone-like material is 0.18-0.34%, the flexural strength is 85.3-103.1 MPa, and the wear resistance test is less than 5 mm.
[0041] The imitation stone material provided by the present invention can be applied to architecture, interior decoration, garden landscape, artwork, etc. Specifically, the imitation stone material can be used as the facade of a building, the door sill, window sill, cabinet countertop, etc. in interior decoration, the walkway, rockery, etc. in garden landscape, and can also be used as the artwork of a vase. When used for artworks such as vases and sculptures, during the preparation process, additives such as pigments, rubbing patterns, etc. can be added according to needs to carry out personalized production.
[0042] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0043] Examples 1-4 all provide a method for preparing a stone-like material, and the raw materials are shown in Table 1.
[0044] Table 1 Raw material composition of Examples 1-4
[0045] The chemical compositions of the raw materials are shown in Table 2.
[0046] Table 2 Chemical composition of raw materials
[0047] Examples 1-4 The preparation method of the imitation stone material provided in Examples 1-4 comprises the following steps: (1) Raw material grinding: wet grinding the raw materials and additives, wherein the additive is a dispersant, specifically, a sodium silicate aqueous solution; (2) Drying: The ground raw materials are fully mixed with the dispersant to obtain a formula slurry, and the slurry is placed in an oven, the oven temperature is adjusted to 110°C, and dried to obtain a powder with a moisture content of 5-7%; (3) Granulation: After drying, the powder is sieved through a 400-mesh sieve and granulated, and aged for 36 hours; (4) Molding: Molding pressure 30MPa, hold pressure for 8 seconds and then demold; (5) Sintering: Heating from room temperature to 850°C at a heating rate of 5°C / min, maintaining the temperature at 850°C for 1 hour, and heating to 1150°C at a heating rate of 5°C / min for 4 hours; (6) Cooling: first cool from the sintering temperature to the crystallization temperature at a rate of 4°C / min, and keep at the crystallization temperature for 4 hours; then cool from the crystallization temperature to room temperature at a rate of 5°C / min.
[0048] Comparative Examples 1-5 Comparative Examples 1-5 all provide a method for preparing a stone-like material, which is basically the same as Examples 1-4, except that the raw material composition is different. The raw material composition of Comparative Examples 1-5 is shown in Table 3.
[0049] Table 3 Raw material composition in Comparative Examples 1-5
[0050] Comparative Example 6 This comparative example provides a method for preparing a stone-like material, which is basically the same as Example 1, except that the particle size of the copper metallurgical slag is 3 mm.
[0051] The results show that when the particle size of copper metallurgical slag is 3 mm, a dense stone-like material cannot be formed by adopting the sintering and cooling process provided by the present invention.
[0052] Test example Test object: the imitation stone materials obtained in Examples 1-4 and Comparative Examples 1-5.
[0053] Test method: (1) Water absorption rate: It is used to examine the compactness of the imitation stone material. The water absorption rate is measured in accordance with the water absorption rate determination method in GB / T3810.6-2016 Test Methods for Ceramic Tiles Part 3: Determination of Water Absorption, Apparent Porosity, Apparent Relative Density and Bulk Density. The smaller the value, the better the compactness of the imitation stone material and the fewer internal voids.
[0054] (2) Flexural strength: The test is conducted in accordance with the method for determining the destructive strength in Part 4 of GB / T3810.6-2016 Test Methods for Ceramic Tiles: Determination of the Modulus of Rupture and Destructive Strength. The larger the numerical value, the better the flexural performance of the imitation stone material.
[0055] (3) Abrasion resistance: This is used to examine the wear resistance of imitation stone materials. The test is carried out in accordance with Part 6 of GB / T3810.6-2016 Test Methods for Ceramic Tiles: Determination of Wear Depth of Unglazed Tiles. The smaller the value, the better the wear resistance of the imitation stone material.
[0056] Test results: See Table 4.
[0057] Table 4 Water absorption, flexural strength and abrasion resistance test results
[0058] Combining the embodiments and comparative examples with Table 4, it can be seen that the water absorption and wear resistance of embodiments 1-4 are significantly lower than those of comparative examples 1-5, and the flexural strength is higher than that of the stone-like materials obtained in comparative examples 1-5, indicating that the stone-like materials prepared by using the raw material composition and proportion provided by the present invention have smaller internal voids, denser structure, higher flexural strength and better wear resistance.
[0059] Compared with Example 1, Comparative Examples 1, 4 and 5, the only difference is whether copper metallurgical slag is added. The results show that the water absorption and wear resistance results of the stone-like material obtained in Example 1 with the addition of copper metallurgical slag are significantly smaller, and the flexural strength is significantly greater, indicating that the addition of copper metallurgical slag in accordance with the present invention can effectively improve the density, flexural strength and wear resistance of the stone-like material, while the density, flexural strength and wear resistance of the stone-like materials obtained in Comparative Examples 1, 4 and 5 without the addition of copper metallurgical slag are worse regardless of whether the amount of other raw materials is adjusted.
[0060] Comparing Example 2 and Comparative Example 2, the only difference is whether waste ceramics are added. The results show that the stone-like material obtained in Example 2 with the addition of waste ceramics has smaller water absorption and wear resistance results and greater flexural strength, which shows that the addition of waste ceramics and waste microcrystalline glass in the present invention produces a synergistic effect. The addition of waste microcrystalline glass and waste ceramics in the manner of the present invention can effectively improve the density, flexural strength and wear resistance of the stone-like material.
[0061] Comparing Example 3 and Comparative Example 3, and Example 4 and Comparative Example 4, although vanadium-titanium metallurgical slag, copper metallurgical slag, waste ceramics and waste microcrystalline glass were added in Comparative Examples 3 and 4, their proportions and amounts were outside the scope of the present application, especially the amounts of vanadium-titanium metallurgical slag and copper metallurgical slag were outside the scope of the present application. The results showed that when the proportions and amounts were within the scope of the present application, the density, flexural strength and wear resistance of the obtained stone-like material were significantly better.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a stone-like material, characterized in that: In parts by weight, the raw materials include 20-40 parts of vanadium-titanium metallurgical slag, 20-40 parts of copper metallurgical slag, and 30-60 parts of nucleating agent; the nucleating agent includes waste microcrystalline glass and waste ceramics in a mass ratio of 1: (0.5-3).
2. The preparation method according to claim 1, characterized in that: The preparation method comprises: powdering, molding, sintering and cooling the raw materials; in, The sintering process is: heating from room temperature to 850-1000°C at a heating rate of 5-10°C / min, and keeping the temperature for at least 0.5 hours; then heating to 1120-1200°C at a rate of 3-8°C / min, and keeping the temperature for 2-5 hours; And / or, the cooling process is: first cooling from the sintering temperature to the crystallization temperature at a rate of 3-5°C / min, and keeping at the crystallization temperature for 1-6h; then cooling from the crystallization temperature to room temperature at a rate of 4-6°C / min.
3. The preparation method according to claim 2, characterized in that: The crystallization temperature is 950-980°C; And / or, keeping warm at the crystallization temperature for 3-4 hours.
4. The preparation method according to claim 2 or 3, characterized in that: The process of powder making is as follows: the raw materials and the dispersant are wet-ground, mixed evenly to obtain a slurry, dried, granulated and aged; Wherein, after granulation, the grinding particle size of the raw material is 325-400 meshes.
5. The preparation method according to claim 4, characterized in that: The slurry is dried at a temperature of 100-120°C; and / or, the moisture content of the powder after drying is 5-7%; And / or, the aging time is 24-48h.
6. The preparation method according to claim 4 or 5, characterized in that: The dispersant is selected from at least one of sodium silicate aqueous solution, sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate.
7. The preparation method according to any one of claims 2 to 6, characterized in that: The molding pressure is 30-40 MPa, and the pressure is maintained for 5-10 seconds.
8. A stone-like material, characterized in that: The method is prepared by any one of claims 1 to 7.
9. Use of the stone-like material according to claim 8 in at least one of architecture, interior decoration, garden landscape and artwork.
10. The use according to claim 9, characterized in that: The application in the building includes at least one of exterior wall facade, interior wall decorative tiles and antique floor tiles; And / or, the application in the interior decoration includes using the imitation stone material as at least one of a door sill, a window sill, and a cabinet countertop; and / or, the application in the garden landscape includes at least one of a walking path, a rockery, and a corridor decoration; And / or, the application in the artwork includes at least one of a vase, a sculpture, and an artifact component.
Citation Information
Patent Citations
Method for preparing microcrystalline foam glass from ceramic polishing waste
CN102086092A
Method for preparing microcrystalline foam glass by using high titanium blast furnace slag and waste glass powder
CN103241955A
Production method for producing microcrystalline glass by using waste glass and smelting waste
CN103395995A
Recycling method of glass ceramic material
CN106430982A
Method for preparing ceramic material by utilizing pyrogenic process smelting copper slag
CN107500727A
Cited By
Method for preparing plate from copper smelting slag and plate
CN121342481A